Immobilisation of an Aspergillus niger derived endo-1,4-Î²-mannanase, Man26A, for the production of prebiotic mannooligosaccharides from soybean meal - Anderson, Amy Sage (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Bioinformatics)
This study investigated the potential for antibiotic alternatives in the form of prebiotics produced from the enzymatic breakdown of soybean meal (SBM). This study first investigated the immobilisation of an endo-1,4-Î²-mannanase derived from Aspergillus niger on glutaraldehyde-activated chitosan nanoparticles (CTS) and glutaraldehyde-activated chitosan-coated magnetic Fe3O4 nanoparticles (MAGS-CTS) - which could be effectively used to hydrolyse the galactomannan contained in SBM in a recyclable manner. The mannooligosaccharides (MOS) produced from the enzymatic digestion of SBM were then analysed for their prebiotic and antimicrobial capabilities to determine whether the strategy employed was capable of promoting and inhibiting probiotic and pathogenic growth, respectively. An Aspergillus niger endo-1,4-Î²-mannanase, Man26A, was confirmed by FTIR (Fourier-transform infrared spectroscopy) and XRD (X-ray powder diffraction) to be immobilised onto CTS and MAGS-CTS by covalent bonding. The immobilisation (%) and activity yields (%) were 81.14% and 35.45%, and 55.75% and 21.17%, respectively. The biochemical properties (pH and temperature optima, and temperature stability) of both the free CTS and MAGS-CTS immobilised Man26A enzymes were evaluated, with the pH optima shifting to a lower pH range after immobilisation (pH 2.0 "“ 3.0 vs. 5.0), while the temperature optima and stabilities remaining unchanged (at 60Â°C). CTS and free enzymes exhibited identical thermal stabilities, maintaining 100% activity for the first 6 hours at 55Â°C, while MAGS-CTS showed an immediate drop in relative activity after the first 30 minutes of incubation. Recyclability analysis revealed that CTS could be effectively reused for six reaction cycles, while the MAGS-CTS immobilised enzyme could only be used once. Both enzymes could be efficiently stored at 4ÂºC, showing a relative residual activity of 73% after 120 hours of storage. Substrate kinetic analysis showed that the free enzyme had the highest catalytic capabilities in hydrolysing locust bean gum (LBG), with the CTS immobilised enzyme was the most efficient in hydrolysing SBM, the insoluble, complex substrate. Sugar residues produced from the hydrolysis of LBG illustrated the effective breakdown of galactomannan to mannobiose (M2), mannotriose (M3), mannotetrose (M4), and mannohexose (M6). SBM-produced sugars analysed via TLC and HPLC indicated that the MOS residues were most probably glucose, galactose, and galactomannans (GM2 and GM3). The SBM-produced sugars were then evaluated for their prebiotic effect, illustrating their successful utilisation as a carbon source by probiotic bacteria; Streptococcus thermophilus, Bacillus subtilis and Lactobacillus bulgaricus. Evaluation of the antimicrobial activities of the SBM-produced sugars digested by probiotics suggested that their metabolites had the potential to be used as an antibiotic alternative. This study therefore illustrated that an endo-1,4-Î²-mannanase derived from Aspergillus niger could be immobilised successfully, for use in a recyclable reaction to produce MOS products. This study also described the successful use of SBM-sugars as a prebiotic, indicating a successful alternative to antibiotic growth promoters (AGP) by illustrating their positive effect on inhibiting growth of pathogenic bacterial species.
Keywords: Aspergillus niger; Soybean meal; Mannosidases; Oligosaccharides; Immobilized microorganisms